2013
DOI: 10.1038/bjc.2013.530
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study evaluating the toxicity and efficacy of single-agent temsirolimus in chemotherapy-naïve castration-resistant prostate cancer

Abstract: Background:The mammalian target of rapamycin (mTOR) pathway is deregulated in castration-resistant prostate cancer (CRPC). We investigated the efficacy and toxicity of temsirolimus, an mTOR inhibitor, in chemotherapy-naïve CRPC.Methods:In this phase II open label study, eligible patients received IV temsirolimus at 25 mg weekly until objective disease progression, unacceptable toxicity or investigator's discretion. Toxicity was assessed every 4 weeks and responses every 8 weeks. Primary end point was calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Finally, a cross-talk between NF-jB and AR indicates the role of the NF-jB signaling pathway in CR progression [68]. Phase II clinical trials of mTOR inhibitors (ridaforolimus, temsirolimus and everolimus), targeting the PI3K pathway in CRPC have not been overwhelming [69][70][71]. Nevertheless, combinatory trials of PI3K and AR inhibition have shown more promising results but may encounter some toxicity issues [72].…”
Section: Outlaw Pathwaymentioning
confidence: 99%
“…Finally, a cross-talk between NF-jB and AR indicates the role of the NF-jB signaling pathway in CR progression [68]. Phase II clinical trials of mTOR inhibitors (ridaforolimus, temsirolimus and everolimus), targeting the PI3K pathway in CRPC have not been overwhelming [69][70][71]. Nevertheless, combinatory trials of PI3K and AR inhibition have shown more promising results but may encounter some toxicity issues [72].…”
Section: Outlaw Pathwaymentioning
confidence: 99%
“…[50] evaluated the effect of temsirolimus, an mTOR inhibitor, in 21 patients with chemotherapy-naïve CRPC. The primary outcome was a composite of overall response rate plus stable disease.…”
Section: Mechanisms Of Androgen Resistancementioning
confidence: 99%
“…temsirolimus, everolimus, ridaforolimus or sapanisertib) have been developed to specifically inhibit mTOR. Two phase II trials showed minimal activity of temsirolimus as a single agent both in chemo-naïve and in docetaxel-treated CRPC patients (Armstrong et al, 2013;Kruczek et al, 2013). This drug was also tested as maintenance treatment following successful docetaxel chemotherapy, and resulted in a median time to treatment failure of 24.3 weeks (Emmenegger et al, 2015).…”
Section: Pi3k-akt-mtor Pathwaymentioning
confidence: 99%